The Emerging Realities in Military Coups in Africa: An Explanation - Abang, Sunday Owen (NIU Journal of Humanities; Vol 7 No 2 (2022): NIU Journal of Humanities, Vol. 7 No. 2, June 2022, 2022)
The need to defend common interests necessitates the presence of the military in any state, including Africa. But the assumption of executive roles by the same military, through coup detat, was a strange phenomenon till massive enlistment of Africans for the First and Second World Wars exposed these fledgling military groups to enhanced military operations worldwide, including intervening in the governance of a state, especially as they have all that is required: the military might, and gun. This study examines the constitutional role of the military and their penchant to meddle in African politics. We also assess the rules of disengagement within the context of civil-military relations. The methodology adopted in this study is descriptive in nature through secondary method of data retrieval, newspapers, journals and magazines. This is with a view to extract the emerging patterns of coup d’état across the continent, and the approaches in handling transitions from year 2000 to January 2022.  The study reveals a recurring factor - failure in leadership, mass protests in reaction to bad governance, flawed elections – as basic causes for the new wave of coup d’état across Africa. We also recommend that the administration of a state is a sole role of the civilian, and the military should be confined to their role, being security. Keywords: Coup detat, Military Intervention, Military Organizations